Pengaruh Pengungkapan CSR terhadap Pengungkapan SDGS yang Dimoderasi Dualitas Gender - Anthony Holly; Fransiskus Eduardus Daromes; Robert Jao; Della Amelia Coeputra (Journal of Financial and Tax, 2024)
The purpose of this study was to analyze the effect of the CSR Committee on SDGs disclosure with Gender Duality as a moderating variable. The data source used is secondary data taken from the sustainability reports of manufacturing companies listed on the Indonesia Stock Exchange for the period 2019 to 2021. The sample selection used a purposive sampling technique, in order to obtain a total sample of 54 companies. The data analysis technique used is Moderated Regression Analysis. The results of this study indicate that the CSR Committee has a positive and significant effect on SDGs disclosure. Gender duality weakens the influence of the CSR Committee on Disclosure of SDGs.